2021
DOI: 10.3390/medicina57080816
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis Associated with Clozapine Treatment: A Case Series and Systematic Review of the Literature

Abstract: Background and Objectives: Clozapine is the only antipsychotic approved for treatment-resistant schizophrenia. Despite its superior efficacy profile as compared with other antipsychotics, clozapine remains underutilized. Clozapine monitoring systems clearly describe the proposed management of clozapine-induced neutropenia; however, no specific mention is made of how to interpret neutrophilic leukocytosis, despite that being a relatively frequent finding. Prescribers unfamiliar with this molecule may misjudge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, there are more cases where the hematological effect of clozapine manifests as leukocytosis and neutrophilia (Lee et al ., 2015; Fabrazzo et al ., 2017). According to one theory, the release of cytokines, including G-CSF, promotes the expression of anti-apoptotic proteins, tipping the scale toward blood cell survival (Fehsel et al ., 2005; Liu et al ., 2011; Paribello et al ., 2021). In a case series reported by Butler et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are more cases where the hematological effect of clozapine manifests as leukocytosis and neutrophilia (Lee et al ., 2015; Fabrazzo et al ., 2017). According to one theory, the release of cytokines, including G-CSF, promotes the expression of anti-apoptotic proteins, tipping the scale toward blood cell survival (Fehsel et al ., 2005; Liu et al ., 2011; Paribello et al ., 2021). In a case series reported by Butler et al .…”
Section: Discussionmentioning
confidence: 99%
“…These conditions weaken the immune system and increase the susceptibility to infections when combined with clozapine. In contrast, some evidence suggests that leukocytosis from clozapine treatment may be harmless, questioning whether preexisting leukopenia exacerbates the risk of agranulocytosis [ 47 ]. Chen et al [ 48 ] emphasized the role of genetic factors in managing clozapine treatment in individuals with preexisting disorders.…”
Section: Impact Of Comorbid Conditions On the Risk Of Agranulocytosis...mentioning
confidence: 99%
“…88 However, its stimulating effects on the hematopoietic system, such as agranulocytosis, leukocytosis, and thrombocytosis, are recognized as significant side effects. 89,90 A follow-up study about clozapine’s stimulating effect on patients’ thrombopoiesis of a 1-year period demonstrated that since the beginning of clozapine treatment in the first week, platelet counts increased synchronically but transiently, and the early spike in platelet counts reflected raised IL-6 levels, which induced thrombopoiesis through the gp130 signaling and interaction with IL-3 and THPO. 91,92 This result suggests that IL-6 might be the crucial factor in clozapine-induced thrombocytosis.…”
Section: Thrombopoiesis Agents With Potential Value Of Clinical Usementioning
confidence: 99%